2018
DOI: 10.1111/maps.13130
|View full text |Cite
|
Sign up to set email alerts
|

On the carrier phase of the “planetary” noble gases: TEM, Raman, and stepped combustion data for acid‐resistant residues from the Saratov (L4) meteorite

Abstract: Acid‐resistant residues (ARR) were separated from the Saratov (L4) meteorite with the aim to shed more light on the origin of the planetary noble gases (the Q‐gases) in meteorites and the nature of their carrier phase (Q‐phase). Eleven fractions were obtained by HCl and HCl+HF etching, ultrasonication, and subsequent density separation of the ARR in isopropanol and isopropanol+NaOH. Two aliquots of the fractions were also treated with H2O2 and HNO3 to investigate any influence of the oxidizing agent on the Q‐g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
(91 reference statements)
0
8
0
Order By: Relevance
“…2013; Fisenko et al. 2018). Lattice spacing indicative of graphene sheets has been observed in IOM and acid‐resistant residue from Saratov and in some cases has been linked to potential Phase Q‐bearing material (Amari et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2013; Fisenko et al. 2018). Lattice spacing indicative of graphene sheets has been observed in IOM and acid‐resistant residue from Saratov and in some cases has been linked to potential Phase Q‐bearing material (Amari et al.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing metamorphism leads to increasing graphitization of the organic matter (e.g., Cody et al 2008), although a range of structures are still seen in IOM extracted from Saratov (L4; Amari et al 2013;Fisenko et al 2018). Lattice spacing indicative of graphene sheets has been observed in IOM and acidresistant residue from Saratov and in some cases has been linked to potential Phase Q-bearing material (Amari et al 2013;Fisenko et al 2018).…”
Section: Carbonaceous Inclusionmentioning
confidence: 99%
“…3.4-3.5 Å. 6 As shown by the simulation results, the emplacement of a large ion in between the sheets leads to the formation of a bulge. The heavier the ion is, the larger this bulge becomes, and, correspondingly, the energy change induced by the ion implantation especially in the case of heavy Xe and Kr ions increases.…”
Section: Modeling Of Ar/kr/xe Behavior In Flat and Curved Graphene Stacksmentioning
confidence: 80%
“…A peculiar and rather abundant component of noble gases in meteorites -the Qcomponent ("Q" stands for "quintessence") is likely a disordered carbonaceous phase with abundant fewlayers graphene stacks. [2][3][4][5][6] It is suggested that noble gases reside between the sheets and although the mechanism(s) of the gases' incorporation is not firmly established, their isotopic ratios strongly suggest that low energy ion implantation of ionized species was very important. One of the most unusual features of the Q-phase is rather strong binding of trapped noble gases (He, Ar, Xe): during step oxidation these gases are released only at 450-500 °C, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation